Kepemimpinan Wanita dalam Cerkak Sang Mayoret Karya Soegiyono MS Dalam Kajian Feminisme - Nugroho, Sri Prihatin; Alfiah, Alfiah (Universitas PGRI Semarang, 2025)
This study describes the female leadership style taken by the female figure in the short story or short story entitled Sang Mayoret by Soegiyono MS published by Djaka Lodang Number 03 on Saturday Legi, 19 June 2021. In this study the author uses feminism theory. Feminism is a women's movement that calls for emancipation or equality and justice for men. In this research, the writer uses qualitative method with literature study. By collecting information on literature review journals of feminism theory in the form of essays, research reports and electronic books that are relevant to the problems being studied. From the discussion, two types of leadership styles can be drawn, namely the feminine leadership style and the masculine leadership style.